Comparison of the Effects of 20 W and 40 W Electrocautery Power on Postoperative Pain Following Internal Thoracic Artery Harvesting in Coronary Bypass Surgery - Ersoy GG (Journal of Pain Research, 2025)
Güler Gülsen Ersoy Department of Cardiovascular Surgery, Faculty of Medicine, Kastamonu University, Kastamonu, TurkeyCorrespondence: Güler Gülsen Ersoy, Department of Cardiovascular Surgery, Faculty of Medicine, Kastamonu University, Kastamonu, 37100, Turkey, Tel +90 532 667 51 12, Email gg.ersoy@hotmail.comPurpose: After coronary artery bypass graft surgery (CABG), patients may experience pain and numbness in the anterior chest wall. These symptoms can negatively impact patients’ quality of life and overall cardiac surgery satisfaction. This study investigates the effect of monopolar electrocautery output power, for hemostasis in the remaining internal thoracic wall after harvesting of the Internal Thoracic Artery (ITA), on postoperative pain in the anterior chest wall.Patients and Methods: This paper examined 100 patients who had ITA harvesting during CABG in a Cardiovascular Surgery Clinic. Patients who were able to comply with postoperative pain tests and had sufficient mental and visual capacity were included in the study. In Group 1 (n: 50) patient, after the ITA was harvested, hemostasis was performed with 20 watt cautery power on the inner wall of the thorax. In Group 2 (n: 50) patients, hemostasis was performed with 40 watt electrocautery power. It was investigated whether there was a difference between these two groups in terms of postoperative drainage amounts and pain in the anterior chest wall with Behavioral Pain Scale (BPS) and Visual Analogue Scale (VAS).Results: No statistically significant difference between Group 1 and Group 2 regarding demographic data and postoperative drainage amounts. However, in Group 1, in patients who hemostasis performed in the inner wall of the thorax with a low cautery power of 20 watts, postoperative pain was statistically significantly lower than in Group 2 in terms of BPS and VAS.Conclusion: After harvesting of the ITA, hemostasis of the thoracic wall with 20 watt low cautery power does not affect the postoperative drainage. Additionally, these patients experience less postoperative pain due to less thermal damage after CABG. Furthermore, lower postoperative pain levels may reduce treatment costs by reducing analgesic requirements and intensive care duration.Keywords: coronary artery bypass, electrocautery, internal thoracic artery